Peran Guru Pendidikan Agama Islam dalam Menginternalisasi Nilai Karakter Islami di SMA Muhammadiyah Imam Syuhodo - Jaya, Mubarak Tegar; Maksum, Muh. Nur Rochim (Kamaya: Jurnal Ilmu Agama, 2026)
Islamic Religious Education (PAI) teachers play a crucial role in internalizing Islamic character values ​​amidst advances in science and technology that bring both benefits and negative impacts. This study aims to describe the role of Islamic Religious Education (PAI) teachers in helping students of Muhammadiyah Islamic Senior High School (SMA Muhammadiyah Islamic Boarding School) Imam Syuhodo internalize Islamic character. This study also aims to describe the supporting and inhibiting elements in the process of internalizing Islamic character values. This study applies a qualitative phenomenological method in the form of field research. Data collection techniques include documentation, interviews, and observation. Muhammadiyah teachers serve as the primary data source. The research findings indicate that Islamic Religious Education (PAI) teachers contribute to the process of internalizing Islamic character in several ways, including as mentors, educators, motivators, evaluators, and facilitators. Some of the tactics used are being role models, practicing worship, providing guidance, and using lecture techniques that highlight motivational stories from Muhammadiyah leaders. Relevant teaching strategies and teacher role models are examples of supporting elements, but lack of student discipline is another major obstacle.